The Instrumental Feature of the Juridical Person and the De-Consideration of its Personality in Civil Law Code and in the Consumer Defense Code - Goldhar, Tatiane Gonçalves Miranda (2013)
Current paper analyzes the function of the juridical person in current Brazilian law. It focuses on the institute of the de-consideration of the personality of the juridical person as a tool in the struggle against abuses practiced by the organization with the aim at promoting an analysis for the ruling of the Civil Code and the Consumer Defense Code.